2018
DOI: 10.22605/rrh4804
|View full text |Cite
|
Sign up to set email alerts
|

The impact of national health insurance coverage on pit and fissure sealing experience

Abstract: Introduction:The purpose of this study was to review the change of supplied amount of oral pit and fissure sealing (PFS) in urban and rural areas of South Korea after including PFS into the list of treatments covered by the National Health Insurance (NHI), and to check whether there is a difference in supplied amount in areas where the dental treatment accessibility is different based on the data of the Korean National Health and Nutritional Examination Survey (KNHANES). Methods: The KNHANES data year used for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…Studies conducted in the aftermath of the insurance expansion confirmed that access to dental service was improved [5][6][7] ; however, disparities in access to services remained. 6,8,9 Currently, few studies have evaluated whether the dental health insurance expansion improved oral health inequalities (not just service access).…”
Section: Introductionmentioning
confidence: 99%
“…Studies conducted in the aftermath of the insurance expansion confirmed that access to dental service was improved [5][6][7] ; however, disparities in access to services remained. 6,8,9 Currently, few studies have evaluated whether the dental health insurance expansion improved oral health inequalities (not just service access).…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have shown that high partial copayments will be particularly burdensome for low-income individuals [25]. The relationship between socioeconomic factors and sealant has weakened after the reimbursement policy, but still existed [10].…”
Section: Classificationmentioning
confidence: 99%
“…In May 2013, the coverage was expanded up to the second molars of children up to 18 years old. Accordingly, the proportion of children aged 6-14 years who received dental sealant increased encouragingly, from 28.7 to 34.9% [16]. A Korean study reported that after the policy implementation, dental sealant increased and untreated caries decreased, especially among lower SEP groups [17].…”
Section: Introductionmentioning
confidence: 99%